Classical mechanics - Goldstein, Herbert, 1922-; Poole, Charles; Safko, John (San Francisco : Addison-Wesley, 2002)
Survey of the elementary principles -- Variational principles and Langrage's equations -- The central force problem -- The kinematics of rigid body motion -- The rigid body equations of motion -- Oscillations -- The classical mechanics of the special theory of relativity -- The Hamilton equations of motion -- Canonical transformation -- Hamilton-Jacobi theory and action-angle variables -- Classical chaos -- Canonical perturbation theory -- Introduction to the Lagrangian and Hamiltonian formulations for continuous systems and fields.
Keywords: Mecánica analítica; Cinemática; Dinámica